Experimenting with experiments : An introduction - Pickering, Andy; Olesen, Finn; Danholt, Peter (STS Encounters, 2021)
From the introduction: This special issue is dedicated to the exploration of experiments and experimentation. It follows a PhD. course entitled “Exploring and performing experiments” that we organized at Department of Digital Design and Information Studies in spring 2019. The course was attended by 12 PhD fellows, and during the course we and the participants decided to produce a special issue based on the participants’ PhD research projects. The literature for the course included a variety of texts and research articles focusing on experiments mainly from the field of Science and Technology Studies (STS). The readings included the work of Ian Hacking, Andy Pickering, Bruno Latour, Steven Shapin and Simon Schaffer, Isabelle Stengers, Shirley Strum and Brian Eno among others. In the call for papers for this issue authors were asked to draw on the literature in the field of STS in order to explore the role of experiments and experimentation in their own projects, and to consider their articles as vehicles for bringing insights from STS to their own fields. The spirit of this special issue is thus one of ‘STS pollination’ by bringing STS to other fields, rather than necessarily being contributions to STS itself. Hopefully it will generate novel insights and contributions and perhaps cross-pollination